Visible-light assisted one-pot preparation of aryl glyoxals from acetoarylones via in-situ arylacyl bromides formation: Selenium-free approach to acetoarylones oxidation. Issue 7 (15th February 2017) - Natarajan, Palani; Manjeet,; Kumar, Naveen; Devi, Sapna; Mer, Kalyani
Graphical abstract: Highlights: Novel visible-light induced synthesis of 6-arylphenanthridines reported. In situ produced aryl diazonium salts have been employed as a source of aryl radicals. 1% [Ru(bpy)3 ]Cl2 used as a photo-redox catalyst. Complete conversion with up to 94% yield was noticed. Abstract: A novel visible-light (blue LEDs: hν  = 425 ± 15 nm) photocatalyzed one-pot method for the synthesis of electronically diverse aryl glyoxals in good to excellent yields from acetoarylones and green regents such as air, vitamin C and dioxane dibromide has been described. In addition, an application of the current methodology has been demonstrated for the oxidation of monoamine oxidase-B inhibitors, i.e., 1-(4-((4-fluorobenzyl)oxy)phenyl)ethanone and 1-(3-((4-chlorobenzyl)oxy)phenyl)ethanone. This finding may serves as a valuable alternative to the traditional acetoarylones oxidation reactions conducted using selenium dioxide a harmful and unselective reagent known to simultaneously oxidize allylic, benzylic, CH3 and so on.